Beneficial influence of Hf and Zr additions to Nb4at%Ta on the vortex pinning of Nb3Sn with and without an O source. (27th February 2019) - Balachandran, Shreyas; Tarantini, Chiara; Lee, Peter J; Kametani, Fumitake; Su, Yi-Feng; Walker, Benjamin; Starch, William L; Larbalestier, David C
Abstract: Here we show that addition of Hf to Nb4Ta can significantly improve the high field performance of Nb3 Sn, making it suitable for dipole magnets for a machine like the 100 TeV Future Circular Collider (FCC). A big challenge of the FCC is that the desired non-Cu critical current density ( J c ) target of 1500  A mm −2 (16 T, 4.2 K) is substantially above the best present Nb3 Sn conductors doped with Ti or Ta (∼1300  A mm −2 in the very best sample of the very best commercial wire). Recent success with internal oxidation of Nb–Zr precursor has shown significant improvement in the layer J c of Nb3 Sn wires, albeit with the complication of providing an internal oxygen diffusion pathway and avoiding degradation of the irreversibility field H Irr . We here extend the Nb1Zr oxidation approach by comparing Zr and Hf additions to the standard Nb4Ta alloy of maximum H c 2 and H Irr . Nb4Ta rods with 1Zr or 1Hf were made into monofilament wires with and without SnO2 and their properties measured over the entire superconducting range at fields up to 31 T. We found that Group IV alloying of Nb4Ta does raise H Irr, though O2 addition still slightly degrades it. As noted in earlier Nb1Zr work with an O source, the pinning force density F p is strongly enhanced and its peak value shifted to higher field by internal oxidation. A surprising result of this work is that we found better properties in Nb4Ta1Hf without SnO2, F pMax achieving 2.35 times that of the standard Nb4Ta alloy, while the oxidized Nb4Ta1Zr alloy achieved 1.54 times that of the Nb4Ta alloy. The highest layer J c (16 T, 4.2 K) of 3700  A mm −2 was found in the SnO2 -free wire made with Nb4Ta1Hf alloy. Using a standard A15 cross-section fraction of 60% for modern powder-in-tube and rod restack process wires, we estimated that a non-Cu J c of 2200  A mm −2 is obtainable in modern conductors, well above the 1500 A mm −2 FCC specification. Moreover, since the best properties were obtained without SnO2, the Nb4Ta1Hf alloy appears to open a straightforward route to enhanced properties in Nb3 Sn wires manufactured by virtually all the presently used commercial routes employed today.